Ultra‐small Tetrametallic Pt‐Pd‐Rh‐Ag Nanoframes with Tunable Behavior for Direct Formic Acid/Methanol Oxidation. Issue 38 (23rd August 2016) - Saleem, Faisal; Ni, Bing; Yong, Yang; Gu, Lin; Wang, Xun
Abstract : Reversible tuning of ultra‐small multimetallic Pt‐Pd‐Rh‐Ag nanoframes is achieved. These nanoframes showed tunable and reversible modes for the oxidation of small organic molecules by simply inducing segregation with adsorbates, such as SO4 2− and OH − . This is the first example of reversible segregation under electrocatalytic conditions in atomic‐sized electrocatalysts. These nanoframes also showed a controllable activity and good stability for the oxidation of small organic molecules.